Urbanization in Perimesopotamian Areas: The Case of Eastern Anatolia - Frangipane, Marcella (1987)
The V. Gordon Childe Colloquium, Mexico, 1986; Tell Habuba Kabira, Arslantepe, Tepecik, Hassek Höyük, Jebel Aruda